PERLINDUNGAN KONSUMEN SEBAGAI HAK ASASI MANUSIA - Laurensius Arliman S (Ensiklopedia of Journal, 2023)
Consumer protection is the goal of a business to be achieved or a situation to be realized. Therefore, consumer protection goals need to be designed and built in a planned and prepared manner from an early age. Consumer protection is also part of human rights. This article uses a normative legal research approach. The results of the research show that the objective of consumer protection includes the activities of creating and implementing a consumer protection system. Consumer protection goals are prepared in stages, starting from awareness to empowerment. The achievement of consumer protection goals does not have to go through stages based on this arrangement, but by looking at the urgency that it is part of human rights. Human Rights means rights that are fundamental. Human rights state that in the human dimension humans have fundamental rights. This fundamental right is firmly attached to the identity of human humanity. Every human being has the right to have that right.Keywords: Protection, Consumers, Human Rights.